theory Tutorial3+ −
imports Lambda+ −
begin+ −
+ −
section {* Formalising Barendregt's Proof of the Substitution Lemma *}+ −
+ −
text {*+ −
Barendregt's proof needs in the variable case a case distinction.+ −
One way to do this in Isar is to use blocks. A block is some sequent+ −
or reasoning steps enclosed in curly braces+ −
+ −
{ \<dots>+ −
+ −
have "statement"+ −
}+ −
+ −
Such a block can contain local assumptions like+ −
+ −
{ assume "A"+ −
assume "B"+ −
\<dots>+ −
have "C" by \<dots>+ −
}+ −
+ −
Where "C" is the last have-statement in this block. The behaviour + −
of such a block to the 'outside' is the implication+ −
+ −
\<lbrakk>A; B\<rbrakk> \<Longrightarrow> "C" + −
+ −
Now if we want to prove a property "smth" using the case-distinctions+ −
P1, P2 and P3 then we can use the following reasoning:+ −
+ −
{ assume "P1"+ −
\<dots>+ −
have "smth"+ −
}+ −
moreover+ −
{ assume "P2"+ −
\<dots>+ −
have "smth"+ −
}+ −
moreover+ −
{ assume "P3"+ −
\<dots>+ −
have "smth"+ −
}+ −
ultimately have "smth" by blast+ −
+ −
The blocks establish the implications+ −
+ −
P1 \<Longrightarrow> smth+ −
P2 \<Longrightarrow> smth+ −
P3 \<Longrightarrow> smth+ −
+ −
If we know that P1, P2 and P3 cover all the cases, that is P1 \<or> P2 \<or> P3 is+ −
true, then we have 'ultimately' established the property "smth" + −
+ −
*}+ −
+ −
section {* EXERCISE 7 *}+ −
+ −
text {*+ −
Fill in the cases 1.2 and 1.3 and the equational reasoning + −
in the lambda-case.+ −
*}+ −
+ −
lemma forget:+ −
shows "atom x \<sharp> t \<Longrightarrow> t[x ::= s] = t"+ −
by (nominal_induct t avoiding: x s rule: lam.strong_induct)+ −
(auto simp add: lam.fresh fresh_at_base)+ −
+ −
lemma fresh_fact:+ −
assumes a: "atom z \<sharp> s"+ −
and b: "z = y \<or> atom z \<sharp> t"+ −
shows "atom z \<sharp> t[y ::= s]"+ −
using a b+ −
by (nominal_induct t avoiding: z y s rule: lam.strong_induct)+ −
(auto simp add: lam.fresh fresh_at_base)+ −
+ −
+ −
lemma + −
assumes a: "x \<noteq> y"+ −
and b: "atom x \<sharp> L"+ −
shows "M[x::=N][y::=L] = M[y::=L][x::=N[y::=L]]"+ −
using a b+ −
proof (nominal_induct M avoiding: x y N L rule: lam.strong_induct)+ −
case (Var z)+ −
have a1: "x \<noteq> y" by fact+ −
have a2: "atom x \<sharp> L" by fact+ −
show "Var z[x::=N][y::=L] = Var z[y::=L][x::=N[y::=L]]" (is "?LHS = ?RHS")+ −
proof -+ −
{ -- {* Case 1.1 *}+ −
assume c1: "z = x"+ −
have "(1)": "?LHS = N[y::=L]" using c1 by simp+ −
have "(2)": "?RHS = N[y::=L]" using c1 a1 by simp+ −
have "?LHS = ?RHS" using "(1)" "(2)" by simp+ −
}+ −
moreover + −
{ -- {* Case 1.2 *}+ −
assume c2: "z = y" "z \<noteq> x" + −
+ −
have "?LHS = ?RHS" sorry+ −
}+ −
moreover + −
{ -- {* Case 1.3 *}+ −
assume c3: "z \<noteq> x" "z \<noteq> y"+ −
+ −
have "?LHS = ?RHS" sorry+ −
}+ −
ultimately show "?LHS = ?RHS" by blast+ −
qed+ −
next+ −
case (Lam z M1) -- {* case 2: lambdas *}+ −
have ih: "\<lbrakk>x \<noteq> y; atom x \<sharp> L\<rbrakk> \<Longrightarrow> M1[x::=N][y::=L] = M1[y::=L][x::=N[y::=L]]" by fact+ −
have a1: "x \<noteq> y" by fact+ −
have a2: "atom x \<sharp> L" by fact+ −
have fs: "atom z \<sharp> x" "atom z \<sharp> y" "atom z \<sharp> N" "atom z \<sharp> L" by fact++ −
then have b: "atom z \<sharp> N[y::=L]" by (simp add: fresh_fact)+ −
show "(Lam [z].M1)[x::=N][y::=L] = (Lam [z].M1)[y::=L][x::=N[y::=L]]" (is "?LHS=?RHS") + −
proof - + −
have "?LHS = \<dots>" sorry+ −
+ −
also have "\<dots> = ?RHS" sorry+ −
finally show "?LHS = ?RHS" by simp+ −
qed+ −
next+ −
case (App M1 M2) -- {* case 3: applications *}+ −
then show "(App M1 M2)[x::=N][y::=L] = (App M1 M2)[y::=L][x::=N[y::=L]]" by simp+ −
qed+ −
+ −
text {* + −
Again the strong induction principle enables Isabelle to find+ −
the proof of the substitution lemma automatically. + −
*}+ −
+ −
lemma substitution_lemma_version: + −
assumes asm: "x \<noteq> y" "atom x \<sharp> L"+ −
shows "M[x::=N][y::=L] = M[y::=L][x::=N[y::=L]]"+ −
using asm + −
by (nominal_induct M avoiding: x y N L rule: lam.strong_induct)+ −
(auto simp add: fresh_fact forget)+ −
+ −
+ −
end+ −